diode laser for excisional biopsy of pyogenic granuloma: a case series - Mahajan, Gaurav; Gautam, Aditi (International Journal of Dental Research, 2017)
Pyogenic granuloma is one of the inflammatory hyperplasias seen in the oral cavity. This term is a misnomer because the lesion is unrelated to infection and in reality arises in response to various stimuli such as low- grade local irritation, traumatic injury or hormonal factors. The clinical diagnosis of such lesion can be quite challenging because of its close resemblance to certain malignancies like peripheral giant cell granuloma, kaposi’s sarcoma, non hodgkin’s lymphoma etc. for excisional biopsy, options available are conventional surgical excision, electrocautery or lasers. In this report, we seek to highlight the therapeutic advantages achieved with a soft tissue diode laser in the treatment of pyogenic granuloma.